Total Design Of Low Cost Aircraft Cabin Simulator - Tan, Chee Fai; Chen, Wei; Rauterberg, Matthias (2010)
Testbed is a platform on which an assortment of experimental tools and products may be deployed and allowed to interact in real-time. Successful tools and products can be identified and developed in an interactive testbed. A testbed also can be defined as an environment that is created for testing and validating purpose. The total design method is the systematic activity oriented, from the market need identification, to the final product that satisfied the need. The activity of total design includes product, process, people and organization [Sapuan 2005]. The aircraft cabin simulator is a testbed that is developed for European project, namely, SEAT (Smart tEchnologies for Stress free Air Travel). The SEAT project aims to develop a new radical approach through integration of cabin systems with multimedia features. The aircraft cabin simulator is fully designed and built by us. The simulator consists of a small scale cabin-like testing platform, an inventory section, a simulation section and a control section. The interior of the aircraft cabin consists of an economy class section, a business class section, a galley and a lavatory. Each passenger seat and the lavatory are provided with a personal entertainment touch screen monitor. An inventory section is used to store the testing related equipments. A sky-like projection environment is created at the external location. In addition, the simulator is built with an innovative low-cost motion platform. The motion platform is used to simulate the flight environment such as taxing, taking off, turbulence, descending and landing. The control section is fully equipped with a state of art computer system that is used to control and monitor the simulator. In this paper, the aircraft cabin simulator was designed with solid modelling software. Five conceptual designs of simulator were developed with 3D solid model. To determine the final design of simulator, the matrix evaluation method was used. The weight of the simulator was obtained through weight analysis. The simulator was successfully designed and built with lower cost compared with the commercial aircraft simulator. The paper is organized as follows: Section 2 describes the current development of commercial aircraft simulator and Section 3 describes the simulator design methodology. Subsequently, conceptual design of simulator follows in Section 4 and scenario of the final concept presented in Section 5. Section 6 describes the final design of aircraft simulator. The paper is concluded in Section 7.